A height measurement uncertainty model for archaeological surveys by aerial photogrammetry. (February 2017) - Daponte, Pasquale; De Vito, Luca; Mazzilli, Gianluca; Picariello, Francesco; Rapuano, Sergio
Highlights: A survey of techniques providing maps and 3D models using drones in the archaeological field. An uncertainty model for height measurements based on UAV aerial photogrammetry. A 3D reconstruction tool according to the proposed model has been developed. Experimental tests have been carried out by means of Pix4Dmapper Pro and the developed 3D reconstruction tool. Abstract: In this paper, an uncertainty estimation model for object height measurement by aerial photogrammetry using Unmanned Aerial Vehicles (UAVs) is proposed. In particular, a procedure to evaluate the height measurement uncertainty and its sources has been designed. In order to evaluate the uncertainty values related to height measurements, experimental tests to obtain repeated measurements have been conducted. Furthermore, an uncertainty propagation model has been developed considering the uncertainty sources affecting the measurement process. An evaluation of each uncertainty source contribution has been obtained by comparing the results of the experimental investigation and the estimation provided by the proposed propagation model. The 3D maps, which provide object height measurements, are generated by a commercial aerial photogrammetry application, the Pix4Dmapper Pro, and a 3D reconstruction application developed ad hoc. The obtained results and a discussion related to each uncertainty source contribution are presented.